The Relation Between Prepregnancy Sexuality and Sexual Function During Pregnancy and the Postpartum Period: A Prospective Study - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2015)
This study examined the relation between sexual functions of women in prepregnancy (before conception) and during pregnancy and the postpartum period. This study was conducted on 59 healthy pregnant women. Participants were followed from the eighth week of gestation to 6 months after delivery. Sexual function during pregnancy and the postpartum period was shown to have a significant linear correlation with prepregnancy sexuality. There was no relation between pregnancy and postpartum sexuality. All of the participants who had prepregnancy sexual dysfunction continued to experience it during pregnancy, and the majority of them had a significant level of sexual dysfunction in the postpartum period. Our results showed that prepregnancy sexuality plays an important role in maintaining sexuality during pregnancy and the postpartum period.
Keywords: INDEX FSFI; CHILDBIRTH; WOMEN; BEHAVIOR; HEALTH; LIFE